Considerable contribution of the Montreal Protocol to declining greenhouse gas emissions from the United States. Issue 15 (14th August 2017) - Hu, Lei; Montzka, Stephen A.; Lehman, Scott J.; Godwin, David S.; Miller, Benjamin R.; Andrews, Arlyn E.; Thoning, Kirk; Miller, John B.; Sweeney, Colm; Siso, Caroline; Elkins, James W.; Hall, Bradley D.; et al.
Abstract: Ozone depleting substances (ODSs) controlled by the Montreal Protocol are potent greenhouse gases (GHGs), as are their substitutes, the hydrofluorocarbons (HFCs). Here we provide for the first time a comprehensive estimate of U.S. emissions of ODSs and HFCs based on precise measurements in discrete air samples from across North America and in the remote atmosphere. Derived emissions show spatial and seasonal variations qualitatively consistent with known uses and largely confirm U.S. Environmental Protection Agency (EPA) national emissions inventories for most gases. The measurement‐based results further indicate a substantial decline of ODS emissions from 2008 to 2014, equivalent to ~50% of the CO2 ‐equivalent decline in combined emissions of CO2 and all other long‐lived GHGs inventoried by the EPA for the same period. Total estimated CO2 ‐equivalent emissions of HFCs were comparable to the sum of ODS emissions in 2014, but can be expected to decline in the future in response to recent policy measures. Key Points: Atmospheric data indicate substantial declines in United States emissions of ozone‐depleting substances owing to the Montreal Protocol The emission decline is also substantial compared to the decline in total emissions of CO2 and other major greenhouse gases Spatial distribution and seasonality of derived emissions for ozone‐depleting gases and hydrofluorocarbons are consistent with their uses